PELAKSANAAN AKAD MURABAHAH BIL WAKALAH PADA PRODUK PEMBIAYAAN KREDIT USAHA RAKYAT (KUR) MIKRO IB DI BANK BRI SYARIAH KCP MAJALAYA - Lestari, Windi Maulidina; Aliyudin, A (Al-Muamalat: Jurnal Ekonomi Syariah, 2020)
ABSTRACT KUR is a government program launched to help Micro Small Medium Enterprises and Cooperatives (UMKM-K) to grow by involving several banks as their channeling institutions. At Bank BRI Syariah KUR is a new product released in 2017 which is a product of working capital and / or investment financing for MSME which has limitations in fulfilling the requirements set by the bank (not yet bankable). In this product, Bank BRI Syariah uses murabaha bil wakalah, where murabahah contract is done before the purchase of goods. The purpose of this research is to know the procedure of murabahah contract implementation on financing product of People's Business Credit and review of DSN MUI's fatwa regarding the implementation of murabahah agreement. Murabahah is a sale of goods for the goods plus an agreed advantage. While wakalah is giving power to the other party to do something. Akad wakalah in murabahah financing has been established in the fatwa of DSN MUI Number 04 / DSN-MUI / IV / 2000 about murabahah. The method used in this research is descriptive method, that is method which describe the implementation of murabaha bil wakalah contract on KUR financing product in Bank BRI Syariah KCP Majalaya. The type of data used in this study is qualitative, ie data on murabaha bil wakalah contract on KUR financing products in Bank BRI Syariah KCP Majalaya. Sources of data used are primary and secondary data, ie literature related to research problems. Data collection techniques used are through interviews and literature study. The result of the research shows that the procedure of murabahah bil wakalah akad in financing of business credit of the people is done through several phases that is starting with initial selection, document checking, until financing decision is made, then done contract, after which fund disbursement process. Meanwhile, the implementation of murabahah agreement in pemburyaan KUR Mikro iB is not fully in accordance with the Fatwa DSN MUI No. 04 / DSN-MUI / IV / 2000 about murabaha because there is a difference between the implementation of fatwa in the first provision point 9, that is if the bank wants to represent customers to buy goods from third parties, akad sale and purchase murabahah must be done after the goods, in principle become the property of the bank.